Association Between Multiple Sclerosis and Risk of Female Sexual Dysfunction: A Systematic Review and Meta-Analysis. Issue 12 (1st November 2018) - Zhao, Shankun; Wang, Jiamin; Liu, Yangzhou; Luo, Lianmin; Zhu, Zhiguo; Li, Ermao; Zhao, Zhigang
Abstract: Introduction: It has been reported that multiple sclerosis (MS) would increase the susceptibility to female sexual dysfunction (FSD). Aim: To assess whether MS was a risk factor for FSD through a comprehensive literature review and meta-analysis. Methods: MEDLINE (PubMed), Embase, Cochrane Library, and PsychINFO databases were systematically searched for all studies reporting sexual function in women with MS. The protocol for this meta-analysis is available from PROSPERO (CRD42018094392). Main Outcome Measures: The association between MS and risk of FSD was summarized using relative risk or standard mean differences with 95% CI. Subgroup and sensitivity analyses were conducted to detect potential bias. Results: Overall, 1, 485 women participants (the mean age ranged from 29.15 to 45.89 years) were included from 9 studies (4 cross-sectional and 5 case-control studies); 826 of them were patients with MS, with a mean disease duration from 2.7 to 16.51 years. Synthesis of results revealed that MS was significantly associated with an increased risk of FSD (relative risk 1.87, 95% CI 1.25–2.78, P  = .002; heterogeneity: I   2  = 89.0%, P < .001). Women with MS had significantly lower values in total Female Sexual Function Index scores as compared with healthy controls (standard mean differences –2.41, 95% CI −3.87 to −0.96, P  = .017; heterogeneity: I   2  = 97.2%, P  = .001). The grading of recommendations assessment, development, and evaluation–relevant outcomes revealed that the absolute effect of MS on FSD was 434 more per 1000 (from 125 more to 888 more); and the overall quality of the evidence was judged as low. Clinical Implications: The present meta-analysis indicates that women patients with MS have a significant elevated risk of sexual dysfunction, which should raise awareness of the potential association between MS and FSD by both neurologists and urologists. Strengths & Limitations: This the first study to summarize all available evidence for combining the odds on the association between MS and the risk of developing FSD. However, all the included studies were observational design, which may downgrade this evidence. Conclusion: Results of this meta-analysis revealed a potential hazardous effect of MS for developing FSD. High-quality stringently controlled studies with large sample size are still warranted to validate this relationship.